Microstrip sierpinski carpet antenna design - Abdullah, Noorsaliza (2005)
Low cost of fabrication and low profile features of microstrip antennas, attract many researchers to investigate the perfonnance of this antenna in various ways. Fractal antenna is a new member in the family of antennas. They have peculiar properties that make them suitable for applications where wideband and multiband are important parameters of the overall perfonnance. Fractal technology allowed us to design miniature antennas and integrate multiple telecommunication services such as cellular ( GSM 900 and GSM 1800 ), wireless LAN, GPS and hiperLAN2 into a single device. Microstrip sierpinski carpet antenna and sierpinski carpet monopole antenna are designed in this project. The main objective of this project is to design a multiband antenna. The design involved simulations, fabrications and measurements. Mathcad 2001 is used to obtain the size of the basic square patch antenna and simulation was done using Micropatch v.2 and Microwave Office. The fabrication and testing was done at Wireless Communication Centre (WCC). Wideband and multiband operation was observed in sierpinski carpet monopole antenna.